Human Herpes virus 7 infections in children. Clinical and laboratory aspects - G. R. Fatkullina; V. A. Anokhin; A. R. Musina (Журнал инфектологии, 2021)
Objective: to study the activity of HSV 1,2, EBV, CMV, HHV6, HHV7 in children of different age groups, to determine the frequency of various symptoms and syndromes in the examined children depending on hhv7 monoinfection and combined herpetic infection in the age aspect.Materials and methods: 56 children aged 2 to 18 years were examined at the state MEDICAL research Institute named after Prof. A. F. Agafonov in Kazan, at the BIOMED medical and diagnostic center in Kazan and at the LUCH children’s clinic in Naberezhnye Chelny (boys accounted for 62.5% of cases, girls-37.5%). Verification of the diagnosis and evaluation of the dynamics of etiological markers of the infectious process in all observed children was performed by PCR. Blood and saliva were examined to detect markers of human herpes virus type 7 (in qualitative PCR), and blood, oropharyngeal flushing, and urine were examined in semiquantitative PCR to determine other viruses from the herpes family (HHV6, CMV, EBV). In enzyme immunoassay is determined At the same time, we studied options for combining laboratory markers of herpesvirus activity and changes in the main laboratory parameters used in routine practice. We studied the dynamics of the observed parameters against the background of complex antiviral therapy for the next 3 months after the initial examination. The frequency of occurrence of various symptoms and syndromes was determined depending on the activity of various representatives of the herpes family, their combination, and the age of the subjects.Results of the study: HHV7-monoinfection is more typical for the age group of 7-14 years. The significance of mixed HHV6+HHV7 infection decreased with age. The combination of activity of 4 herpesviruses was more often registered in the age categories 2-7 years and 14-18 years. More often, patients had tonsillitis, generalized cervical lymphadenopathy, periodic temperature rise to subfebrile or febrile numbers, pharyngitis, recurrent ARI, rhinitis, which allows us to consider them as the main manifestations of HHV7 infection.Conclusion: HHV7 infection is significant in the modern pathology of the child. The presence of such syndromes as recurrent tonsillitis, cervical lymphadenopathy or isolated enlargement of submandibular lymph nodes, periodic fever, pharyngitis, recurrent ARI in combination with hepato - and/ or splenomegaly, fatigue, and headache is often associated with HHV7. HHV7-viremia is relatively rare, despite obvious clinical and laboratory signs of inflammation indicating the presence of a viral disease, which, apparently, and is the cause of underdiagnosis and lack of proper attention to this infection.